IJIS Edu : Indonesian J. Integr. Sci. Education, 3 (2) 2021 Copyright © 2021, IJIS Edu : Indonesian Journal of Science Education 149 Ethnoecology Local Communities on Kasboyo Lake: Exploration of Conservation Values Using the Ethnoscience Approach as a Source of Natural Science Learning - Ilhami, Aldeva; Suci, Defriyanitha Anggraini; Melianti, Melianti; Fernando, Adam; Pernantah, Piki Setri (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
Local wisdom has noble values that apply to community life, such as protecting and managing theenvironment in a sustainable manner. Human efforts in adapting, managing, and living in harmony withtheir environment are known as ethnoecology. The study aimed to analyze the conservation values of theKasboyo lake ecosystem in Kampar district, Riau. This study used a case study design with a qualitativeapproach. Data collection was carried out in the Simpang Petai Village, Rumbio Jaya District, KamparRegency, Riau Province. The research subjects consisted of six people consisting of traditional leaders,village officials, and local communities with snowball sampling. Data collection techniques using interviews,observation, and documentation. Data analysis uses the Miles-Huberman model, including data reduction,display, and concluding. The results showed that the local community had an agreement with the prohibitionof fishing, waste disposal, and environmental destruction. The local communities around the Kasboyo Lakearea have applied conservation principles. Local community knowledge contains conservation values,including environmental care, creativity, and humanism. So it is hoped that this local wisdom can be usedas a source of science learning to foster students' conservation character